대학 신입생의 흡연 실태와 금연 프로그램 운영 방안 - 최구윤(Gui Yun Choi); 이경희(Kyung Hee Lee) (지역사회간호학회지, 2007)
Purpose: Based on the results of a survey on college freshmen's smoking this study examined the application of smoking cessation programs. Methods: The opinions of 89 smokers who were college freshmen were investigated and analyzed using a survey questionnaire. Results: Among the survey respondents, the largest percentage (47.2%) replied 'little satisfied' to the question on the with campus life. Of the participants, 57.3% considered that their health state was bad because of smoking. As to motives for smoking, 'curiosity' was most frequent. Smokers had more smoking friends than nonsmoking ones. The 82% of the smokers had experience in stopping smoking. Among smoking cessation methods, the self overcoming was most frequent(50.6%). During the survey, 28 smokers applied for the cessation program and they favored e-mails for information. E-mails were sent to them once in a week for 6 weeks and short messages were sent to their cell phone in order to encourage them to read the e-mails. Conclusions: To encourage and maintain smoking cessation, it is recommended to have a personalized or small group program. More researches are needed to execute the program and evaluate results. Colleges need to have an innovative approach on smoking prevention and cessation services.